2015
DOI: 10.1055/s-0035-1564587
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medication Use in Very Low-Birth-Weight Infants in a Level 3 NICU over 2 Decades

Abstract: The trends of overall medication use remained the same in our neonatal intensive care unit (NICU) over the past 22 years. There was no association between medication utilization and survival. VLBW infants continue to receive a high number of medications in the NICU, including a variety of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The study periods varied from one month [26,55,67,68] to studies spanning over 22 years [33]. The median (interquartile range, IQR) duration of data collection in 79 studies was 6 (3-18) months.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The study periods varied from one month [26,55,67,68] to studies spanning over 22 years [33]. The median (interquartile range, IQR) duration of data collection in 79 studies was 6 (3-18) months.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Several studies (27 studies) [8,11,13,19,20,22,23,26,28,32,34,[37][38][39][42][43][44][45]50,59,63,[67][68][69]71,73,75] reported the maximum number of drugs received by at least one infant: Kumar et al [38] reported the highest drug burden with at least one infant receiving 62 individual drugs, while 8 other studies [13,20,22,23,28,32,43,50] reported that the maximum number of drug per infant was ≥30 in their population. The study periods varied from one month [26,55,67,68] to studies spanning over 22 years [33]. The median (interquartile range, IQR) duration of data collection in 79 studies was 6 (3-18) months.…”
Section: Number Of Drugs Per Infantmentioning
confidence: 99%
See 2 more Smart Citations
“…point for clinical trials on the most commonly used off-label medications, and to better identify infants at highest risk of medication over-prescribing and adverse drug events. While a majority of the published studies provide data on frequency of on-and off-label medication use in the NICU, 7 very few identify clinical and demographic predictors of receiving a higher number of medications. The objective of this study was to not only quantify medication utilization in very low birth weight (<1,500 g) preterm infants but to also identify risk factors associated with the highest quartile of medication exposure.…”
mentioning
confidence: 99%